1999
DOI: 10.1021/bi9900370
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for the K+-Induced Macromolecular Structure of Guanosine 5‘-Monophosphate in Solution

Abstract: The 31 P NMR spectra of (TMA) 2 (5′-GMP), where TMA is [(CH 3 ) 4 N] + and 5′-GMP is guanosine 5′-monophosphate, and K 2 (5′-GMP), containing various amounts of KCl or TMACl, have been obtained at 2 °C. Variable-temperature spectra have also been obtained for K 2 (5′-GMP). The TMA + ion serves to neutralize the charge on the dianionic 5′-GMP and permits the added K + to bond preferentially in structureforming sites. 1 H NMR spectra (one-and two-dimensional) have been obtained for K 2 (5′-GMP) and used to assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 37 publications
5
71
0
1
Order By: Relevance
“…Previous 31 P NMR measurements revealed that at T ¼ 25 C only 13.6% of the molecules are involved into the formation of columnar stacks [4]. Temperature dependent ''melting'' behavior of guanosine stacks has been also observed by other experimental methods, for example NMR spectroscopy [7][8][9], interferometric DLS [10], X-ray and circular dichroism spectroscopy [11][12][13][14], and is in agreement with out observations.…”
Section: Discussionsupporting
confidence: 87%
“…Previous 31 P NMR measurements revealed that at T ¼ 25 C only 13.6% of the molecules are involved into the formation of columnar stacks [4]. Temperature dependent ''melting'' behavior of guanosine stacks has been also observed by other experimental methods, for example NMR spectroscopy [7][8][9], interferometric DLS [10], X-ray and circular dichroism spectroscopy [11][12][13][14], and is in agreement with out observations.…”
Section: Discussionsupporting
confidence: 87%
“…It has been observed that the proportion of helix to G4 increases with increasing K + (Hightower et al, 2009). Additionally, the structure of the tetrads in the two salts is different (Hightower et al, 2009); in Na + the tetrads alternate between C3¢-endo (anti) and C2¢-endo (syn) sugar conformations (Wu and Kwan, 2009), while in K + they are all anti, consistent with a parallel arrangement or a continuous helix (Walmsley and Burnett, 1999). Interestingly, the solutions of GMPdss with NaH 2 PO 4 and KH 2 PO 4 tend to establish the low and high ends, respectively, of thermal stability and CD shape and peak magnitude, which bracket the solutions of GMPdss/XMPfa (with the exception of X = G).…”
Section: Discussionmentioning
confidence: 95%
“…It is not surprising that Na + and K + would favor different structures. Na + is smaller than K + and fits into the center of a single tetrad, whereas the larger K + occupies the space between two tetrads (Walmsley and Burnett, 1999;Panda and Walmsley, 2011). Another consideration is the competition between G-tetrads and the continuous helix, which is promoted by K + (Walmsley and Burnett, 1999), although it may also occur in the presence of Na + (Sasisekharan et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it might seem more reasonable for the TMA + ion to interact with the negative phosphate groups, it is known that the interaction of this cation with 5′AMP and 5′GMP is electrostatic only 42 and that it does not affect the phosphate chemical shift in aqueous solution. 43 On the other hand, the tetrabutylammonium ion did not bond at all; apparently it is too large to fit in the cavity.…”
Section: -Propanol As a Guestmentioning
confidence: 99%